A psychometric evaluation of Chinese chronic hepatitis B virus infection-related stigma scale using classical test theory and item response theory - Zhong, Sirui; Zhou, Yuxiao; Zhumajiang, Wuerken; Feng, Lifen; Gu, Jing; Lin, Xiao; Hao, Yuantao (Frontiers in Psychology, 2023)
Purpose To validate the hepatitis B virus infection-related stigma scale (HBVISS) using Classical Test Theory and Item Response Theory in a sample of Chinese chronic HBV carriers. Methods Feasibility, internal consistency reliability, split-half reliability and construct validity were evaluated using a cross-sectional validation study (n = 1,058) in Classical Test Theory. Content validity was assessed by COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) criteria. The Item Response Theory (IRT) model parameters were estimated using Samejima’s graded response model, after which item response category characteristic curves were drawn. Item information, test information, and IRT-based marginal reliability were calculated. Measurement invariance was assessed using differential item functioning (DIF). SPSS and R software were used for the analysis. Results The response rate reached 96.4% and the scale was completed in an average time of 5 min. Content validity of HBVISS was sufficient (+) and the quality of the evidence was high according to COSMIN criteria. Confirmatory factor analysis showed acceptable goodness-of-fit (χ2/df = 5.40, standardized root mean square residual = 0.057, root mean square error of approximation = 0.064, goodness-of-fit index = 0.902, comparative fit index = 0.925, incremental fit index = 0.926, and Tucker-Lewis index = 0.912). Cronbach’s α fell in the range of 0.79–0.89 for each dimension and 0.93 for the total scale. Split-half reliability was 0.96. IRT discrimination parameters were estimated to range between 0.959 and 2.333, and the threshold parameters were in the range-3.767 to 3.894. The average score for test information was 12.75 (information >10) when the theta level reached between-4 and + 4. The IRT-based marginal reliability was 0.95 for the total scale and fell in the range of 0.83–0.91 for each dimension. No measurement invariance was detected (d-R2 < 0.02). Conclusion HBVISS exhibited good feasibility, reliability, validity, and item quality, making it suitable for assessing chronic Hepatitis B virus infection-related stigma.